Providing Legal Protection To Depriminants From Actions of Violence Between Prisoners - Faizal Badri Nugroho; Priambodo Adi Wibowo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The background factors arise victims of acts of violence between prisoners. So it is necessary to protect the inmates who experience violence in correctional institutions. Prevention efforts are carried out by correctional institutions to prevent and reduce victims and prevent riots from occurring in correctional institutions in order to achieve the goal of peace law. The research method of writing uses normative research methods, conducting library research, namely legal research by researching and conducting searches legal literature as well as analyzing secondary data, the aim is to obtain accurate data or truth in order to obtain permanent legal certainty. Library Materials: Primary Legal Materials and Secondary Legal Materials. The efforts made by the Surabaya Class I Correctional Institution are divided into two, namely repressive and preventive. Repressive efforts are efforts to deal with after the occurrence of violations committed by convicts and detainees, while preventive efforts are efforts made before the occurrence of violations committed by convicts and detainees in prisons. Consists of: Repressive Efforts: Preventive Efforts: Facilities and infrastructure are still below sufficient to meet the needs of students and not only facilities and infrastructure for convicts and detainees, facilities and infrastructure for workers in prison offices also experience a shortage of equipment to strive for better performance well, to add insight through television is constrained by increasing electricity costs. All service improvements are difficult to materialize without the support of the Government and the Community.